Starzeć się pięknie, czyli jak? Słów kilka o estetyzacji starzejącego się ciała seniora - Kramkowska, Emilia (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Aestheticization is a process in which something “non-aesthetic” is made or is made to be understood as something aesthetic. This global trend is on the increase, and now it also covers human body. The indisputably advancing ageing processes in contemporary societies provoke a question how to understand the process of aestheticization of an aging human body? The paper offers a survey of opinions expressed by the researched elderly – aged 60 and over – concerning the process of aestheticization of the aging human body. The comparative, quantitative research was held in Poland, Bulgaria and Portugal. The research results show that the national background of the subjects strongly affects their opinions on the issues under study. The elderly from Portugal expressed the most positive view of the of corporeal aestheticization, while the Bulgarian seniors assessed these issues in the most critical fashion. The Polish group represented a middle position.